The effects of perceived sport environment on sport gains of Chinese university students: chain mediation between physical activity behavior and sport learning self-efficacy - Wu, Liang; Gao, Jia; Xiang, Jun (Frontiers in Psychology, 2024)
Introduction Sports gains reflect the sports development of college students, which is a direct reflection of the quality of school sports work, while the perception of sports environment, physical activity behavior, and self-efficacy in sports learning are closely related to their sports gains, which directly affects their effectiveness and interest in sports learning. Objective To investigate the effects of perceived sports environment on Chinese college students’ sport gains, and to verify the mediating roles of physical activity behavior and self-efficacy in sport learning. Methods A survey of 2,207 Chinese university students was conducted using the sport environment perception scale, sport gain scale, physical activity behavior scale, and sport learning self-efficacy scale. Results (1) There were significant differences in age and gender between college students’ perceptions of sport environment, sport gains, sport exercise behavior, and sport learning self-efficacy, and the mean scores of each scale were better for male students than for female students. (2) Perception of sports environment was significantly positively correlated with sports gain, and perception of sports environment had a direct positive effect on sports gain. In addition, sport environment perception positively predicted physical activity behavior and sport learning self-efficacy; physical activity behavior significantly predicted sport learning self-efficacy and sport gains; physical learning self-efficacy was a significant positive predictor of sport gains. (3) Physical activity behavior and physical learning self-efficacy played a significant chained mediating role between perceived physical environment and physical gains. These results are important for promoting physical education learning outcomes among college students and provide a theoretical basis for developing interventions. However, there are limitations to this study, such as the specificity of the sample and the self-reported data used. Future research could expand the sample and utilize multiple assessment methods to validate these results.